Framing gender: Representing male teachers in the Australian and New Zealand press. (1st June 2019) - Reid, Donald; Palmer, Catherine; Drummond, Murray; Cruickshank, Vaughan
Over the past two decades the issue of gender imbalance in teaching has been the subject of media and political discussion. Researchers have yet to draw definitive conclusions as to the relationship between teacher gender and student achievement, but the notion that more men are needed in teaching persists, with calls for governments to enact 'affirmative action' policies. Despite this, surveys of male teachers have found that many believe they are portrayed negatively in the media and that they are under greater scrutiny than their female counterparts. In seeking to better understand this contradiction, this article examines 233 news stories covering the issue of men in teaching. Using framing theory, the authors found that despite a high percentage of stories carrying a positive angle, male teachers are predominantly framed in problematic ways. The authors argue that the news media is ideologically limited in its representation of male teachers, resulting in any advocacy being a counter-narrative to the prevailing logic.